Ocean warming, icebergs, and productivity in the Gulf of Alaska during the Last Interglacial - Sánchez Montes, Maria Luisa; McClymont, Erin L.; Asahi, Hirofumi; Stoner, Joseph; Moy, Christopher M.; Gleghorn, Sophie; Lloyd, Jerry M. (Frontiers in Earth Science, 2025)
The Pacific Ocean is an important region for carbon storage, yet the past ocean–climate interactions are relatively underexplored in explaining glacial/interglacial climate variability during the late Pleistocene re-expansion of the Cordilleran Ice Sheet (CIS). We analysed marine sediment samples from IODP 341 Expedition Site U1418 in the Gulf of Alaska (GOA) using marine and terrestrial biomarkers to study the periodicity of glacial–interglacial cycles over the last 500 thousand years and reconstruct the North Pacific oceanography and marine productivity. Our sea surface temperature (SST) results show that marine isotope stages (MISs) 4 and 6 are the coldest and freshest glacials and MIS 5 and MIS 1 are the warmest and saltiest interglacials. The glacial–interglacials during the last 200 kyr are best observed due to increased sedimentation rates in the GOA during the expansion of the CIS, when coccolithophores increase relative to diatom productivity export. We observe lower %IRDs during cold MIS 6 than during warm MIS 5, and overall lower carbon and nitrogen accumulation rates (TOC and TN MAR) and stable isotope ratios (δ15N and δ13C). We conclude that during MIS 6, the stratification of the cold and fresh surface ocean helped the growth of the CIS, and coccolithophores did not fully exploit the nutrient availability in the ocean but contributed to deep carbon storage and climate cooling. During MIS 5, although SSTs were 6°C warmer, icebergs were more abundant. We infer that higher coccolithophore abundance with different alkenone configurations suggests a change in the dominant coccolithophore groups and changes in the available nutrients, probably as a result of higher influence of the more saline Alaska Current (AC) and lower influence of the Alaska Coastal Current (ACC) at Site U1418. This higher AC influence in the GOA contributed to sedimentary carbon storage and contributed to climate cooling despite the warm climate and higher iceberg discharge. As the last interglacial (MIS 5e) was a time period with similar than modern atmospheric CO2 concentrations, our results provide new understandings of the possible behaviours of CIS and GOA under the current changes in climate.